CircHN1 affects cell proliferation and migration in gastric cancer. Issue 10 (1st July 2020) - Zhang, Yu; Wang, Maoye; Zang, Xueyan; Mao, Zheying; Chen, Yanke; Mao, Fei; Qian, Hui; Xu, Wenrong; Zhang, Xu
Abstract: Background: Increasing evidence indicates that circular RNAs (circRNAs) are dysregulated in human cancers. The biological roles of circRNAs in gastric cancer (GC) have not been well‐characterized. Methods: The GEO database was used to analyze circRNA expression profile in GC. The expression level of target circRNA in tumor tissues and adjacent non‐tumor tissues was detected by reverse transcription‐quantitative PCR. Gene transfection was used to manipulate the expression of circRNAs. The biological roles of circRNAs in cell proliferation, migration, and invasion were determined by cell counting, colony formation, transwell migration, Matrigel invasion, and mouse xenograft tumor assays. The interactions between circRNAs and miRNAs were verified by RNA immunoprecipitation and luciferase reporter assays. Results: We found that circHN1 was upregulated in GC tissues and cell lines compared to adjacent non‐tumor tissues and normal gastric epithelial cells. Additionally, circHN1 silencing significantly promoted GC cell growth, colony formation, migration, and invasion, whereas circHN1 overexpression had the opposite effects. CircHN1 overexpression also suppressed gastric cancer growth in the mouse xenograft tumor model. CircHN1 was mainly localized in the cytoplasm of GC cells and could bind to AGO2. MiR‐1248 and miR‐375 were predicted to interact with circHN1 by bioinformatic analyses. MiR‐1248 and miR‐375 overexpression inhibited the activity of the circHN1 luciferase reporter. Conclusion: CircHN1 is aberrantly expressed in GC and affects the proliferation and migration of gastric cancer cells by acting as miRNA sponge.